2018
DOI: 10.30526/2017.ihsciconf.1767
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tox A gene in Pseudomonas aeruginosa that isolates from different clinical cases by using PCR.

Abstract: Current study obtained (75) isolate of Pseudomonas aeruginosa collected from different cases included : 28 isolates from otitis media, 23 isolates from burn infections, 10 isolates from wound infections, 8 isolates from urinary tract infections and 6 isolates from blood, during the period between 1/9/2014 to 1/11/2014        The result revealed that the tox A gene was present in 54 isolates (72%) of Pseudomonas aeruginosa. The gel electrophoresis showed that the molecular weight of tox A gene was 352 bp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…The inhibitory effect of Pyocyanin from precipitate and filtrate on the growth of S.aureus indicates the ability of P.aeruginosa to produce Pyocyanin pigment (Qasim et al, 2009). As shown in Figure (7). This result is close to that of (Iwalokun et al, 2006) who obtained 81.5% of their Pyocyanin-producing isolates.…”
Section: Detection the Ability Of P Aeruginosa To Produce Pyocyanin P...supporting
confidence: 91%
“…The inhibitory effect of Pyocyanin from precipitate and filtrate on the growth of S.aureus indicates the ability of P.aeruginosa to produce Pyocyanin pigment (Qasim et al, 2009). As shown in Figure (7). This result is close to that of (Iwalokun et al, 2006) who obtained 81.5% of their Pyocyanin-producing isolates.…”
Section: Detection the Ability Of P Aeruginosa To Produce Pyocyanin P...supporting
confidence: 91%
“…The results of the current study were consistent with the results of (17). Whereas, P. aeruginosa isolates showed high resistance to Ceftazidime (81%), Cefotaxime (78%), Piperacillin (76%) and were resistant to Ciprofloxacin, Tobramycin (74%) and Genamicin (72%).…”
Section: 2supporting
confidence: 90%
“…The mexR gene was also detected in 100 % isolates in the current study, which was in line with literature. 22 The current findings showed that some clinical specimens had a greater relative frequency of virulence genes. It has been hypothesised that the location of the infection and the duration of the illness can result in the development of some virulence determinants, which in turn affects how virulent P. aeruginosa clinical isolates are.…”
Section: Discussionmentioning
confidence: 52%